A circulação da Educação Física nas reuniões da Anped (2017-2021) - Curcino, Thiago Pinheiro (Universidade Federal do Tocantins, 2023)
The present work carried out a documental study, having as data source the annals produced in the meetings of the National Association of Graduate Studies and Research in Education (Anped). Thus, the meetings covering the period from 2017 to 2021 were selected for this study. The technique used to organize and analyze the data was bibliometrics, with the following indicators: authors, titles, linked institutions and year of publication. The presence of researchers from the field of physical education at this event raised the issue of understanding how work on Physical Education has been disseminated at Anped meetings. The results of the analyzes revealed that the publications follow a rhythm of 4 to 5 works published per edition of the event, considering the last three meetings in the period analyzed here, which seems to be scarce numbers, taking into account the scope and relevance of the event. Regarding the authors, we found that, on average, in the period from 2017 to 2021, they published only once, with the exception of the author Ana Paula da Silva Santos, who published two works. Data on the regional distribution of research revealed regional asymmetries in relation to scientific production where the South and Southeast regions together represented 80% of the works published in the three editions of the meeting, while the regions: North comprises 8%, Midwest 15 % and Northeast 0% of publications. About what the works published in Anped say, we discovered from the “word cloud” produced in the Iramuteq software that the most recurrent terms in the studies were, in the first place, Education, Young People, Adults. Second comes Curriculum and Teacher Training. The works with the recurrence of the words Youth and Adults articulated the discussion using narrative methodologies, which employ interviews as a data collection instrument, while the works that focused on the theme Curriculum and Teacher Training developed the research through documentary studies.